El Tribunal Europeo de Derechos Humanos y el 40 aniversario de la Constitución española (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
This paper will focus on the impact produced by the European Court of Human Rights case-law on the interpretation adopted by the Constitutional Court regarding fundamental rights laid down in the Spanish Constitution. On the occasion of honoring the almost simultaneous 40th anniversary of Spain becoming a Member State of the Council of Europe and passing the Spanish Constitution (1977 and 1978, respectively), the positive impact of the European Court of Human Rights case-law is assessed. Although the purpose is not to carry out an exhaustive assessment of the case-law, this paper nevertheless appraises the study of three current topics through the fruitful interaction between the European Court system and the Spanish Constitutional order. Firstly, the configuration of an amparo appeal [an appeal for legal protection of fundamental rights] following the reform operated by Organic Law 6/2007, of 24 May, amending Organic Law on the Constitutional Court, and the European Court of Human Rights, that is, addressing the concept of special constitutional importance as a requirement for admissibility of amparo appeals, and the non-existence of such requirement within the system of the Rome Convention. Secondly, a controversial issue not yet solved by the constitutional doctrine is addressed, namely the creation of new rights from the case-law of the European Court of Human Rights. Finally, the late reform introduced in the Spanish legal system in order to enforce judgements of the European Court of Human Rights within the internal legal order is also assessed, which supplements the control system for enforcing judgements adopted by the Council of Europe.
Keywords: Fundamental Rights; Constitutional Court; European Court of Human Rights; Convention for the Protection of Human Rights and Fundamental Freedoms signed in Rome in 1950; amparo appeal; enforcement of judgments delivered by the European Court of Human Right